The hidden treasure in your data: phasing with unexpected weak anomalous scatterers from routine data sets. Issue 4 (1st April 2017) - Hegde, Raghurama P.; Fedorov, Alexander A.; Sauder, J. Michael; Burley, Stephen K.; Almo, Steven C.; Ramagopal, Udupi A.
Abstract : Weak anomalous signals from serendipitously acquired surface‐bound Ca atoms/native S atoms from routine data sets, that were not optimized for SAD phasing, were used to successfully phase protein structures. Abstract : Single‐wavelength anomalous dispersion (SAD) utilizing anomalous signal from native S atoms, or other atoms with Z ≤ 20, generally requires highly redundant data collected using relatively long‐wavelength X‐rays. Here, the results from two proteins are presented where the anomalous signal from serendipitously acquired surface‐bound Ca atoms with an anomalous data multiplicity of around 10 was utilized to drive de novo structure determination. In both cases, the Ca atoms were acquired from the crystallization solution, and the data‐collection strategy was not optimized to exploit the anomalous signal from these scatterers. The X‐ray data were collected at 0.98 Å wavelength in one case and at 1.74 Å in the other (the wavelength was optimized for sulfur, but the anomalous signal from calcium was exploited for structure solution). Similarly, using a test case, it is shown that data collected at ∼1.0 Å wavelength, where the f ′′ value for sulfur is 0.28 e, are sufficient for structure determination using intrinsic S atoms from a strongly diffracting crystal. Interestingly, it was also observed that SHELXD was capable of generating a substructure solution from high‐exposure data with a completeness of 70% for low‐resolution reflections extending to 3.5 Å resolution with relatively low anomalous multiplicity. Considering the fact that many crystallization conditions contain anomalous scatterers such as Cl, Ca, Mn etc., checking for the presence of fortuitous anomalous signal in data from well diffracting crystals could prove useful in either determining the structure de novo or in accurately assigning surface‐bound atoms.